Impacts of commingling preconditioned and auction-derived beef calves on bovine respiratory disease related morbidity, mortality, and weight gain - Mijar, Sanjaya; van der Meer, Frank; Pajor, Ed; Hodder, Abigail; Louden, Julia Morgan; Thompson, Sean; Orsel, Karin (Frontiers in Veterinary Science, 2023)
Stressors predisposing to bovine respiratory disease (BRD) upon arrival in the feedlot, include the ranch to feedlot transition and mixing cattle from multiple sources. Preconditioning (PC) reduces multiple stressors, but commingling PC and auction-derived (AD) calves in a feedlot may increase BRD risk. Our objective was to evaluate PC calf performance over the first 40 days in the feedlot and determine impacts of commingling with varying proportions of AD calves (25, 50, and 75%). Calves were either preconditioned at one ranch (n=250) or mixed-source and bought from a local auction (n=250). At arrival, calves were assigned into 1 of 5 pens: 100PC, 75PC, 50PC, 25PC and 0PC, reflecting the percentage of PC calves in a 100-head pen. Over 40 days, morbidity in pen 100PC was lower compared to 0PC (24 versus 50%, P<0.001) and varied in commingled pens, being highest (63%) in 25PC and least (21%) in 50PC (P<0.05). There were 3 AD deaths in 0PC and 2 deaths in 25PC. The AD calves in 0PC were 3 times more likely to get BRD than PC calves in 100PC; however, AD calves gained 0.49 kg/d more than PC calves (P<0.0001). Ignoring pen placement, AD calves were 2.76 times more likely to get BRD but gained 0.27 kg/d more than PC calves (P<0.0001). Commingling did not affect morbidity of PC (P=0.5) or AD calves (P=0.96), implying commingling did not affect health. Calves in 25PC were 3.39 times more likely to get BRD than those in the 100PC (P<0.001). Furthermore, 25PC calves gained the most (1.08 kg/d), followed by 50PC (0.62 kg/d) and 75PC (0.61 kg/d), compared to 100PC (P<0.05). Calf weight at arrival modified ADG (P<0.05). In conclusion, PC calves had lower morbidity over the first 40 days, irrespective of commingling. With larger variations in arrival weight, there was no advantage of PC for ADG in the first 40 days. The unknown weaning strategies and comparable arrival weights of AD calves may have contributed to greater ADG in AD calves.